Acquiring higher lumen efficacy and color rendering index with green NaYF4:Er3+Yb3+ and red α-SrO·3B2O3:Sm2+ layers for designing remote phosphor LED - My Hanh Nguyen Thi; Nguyen Thi Phuong Loan; Nguyen Doan Quoc Anh (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Lighting devices that apply diodes to create white light-emitting diodes (WLEDs) can achieve remarkable results in color quality, especially those containing quantum dots (QDs) and phosphor. The technique to create an appropriate package is providing spaces between the QDs and phosphor components which helps decrease the ratio of the reabsorption losses and keeps the QDs surface ligands constant. The research aims to perfect the constructing method of remote phosphor configuration containing quantum dots and phosphor materials that based on lighting properties and temperature feature of WLEDs. The infrared thermography is the tool to measure and analyze total emitted light and emission ranges of the device. This device is also used in temperature simulation and experimental verification. At the given mA of 60, the WLEDs structure with green QDs layer above the phosphor layer results in 996 lm luminous flux (LF), and Ra = 57 in color rendering ability. Meanwhile, luminous flux of WLEDs with red QDs-on-phosphor structure is 632, and Ra = 70. Furthermore, comparing with the green QDs-on-phosphor type, the red QDs-on-phosphor type emitted less LF. However, the red QDs-on-phosphor type can be the most effective package design to achieve color rendering ability.